Śrī Phārbasa Gujarātī Sabhā mahotsava grantha : 75 varshanī sāhityapravrtti nimitta - Jānī, Ambālāla Bulākhīrāma, 1880- (Śrī Phôrbasa Gujarāti Sabhā granthamālā, 1940)
Seventy-fifth anniversary celebration volume of the Shree Forbes Gujarati Sabha; comprises articles on the civilization of Gujarat, India.